Water-induced hydrogenation of graphene/metal interfaces at room temperature: Insights on water intercalation and identification of sites for water splitting - He, Guangyu; Wang, Qi; Yu, Hak Ki; Farías, Daniel; Liu, Yingchun; Politano, Antonio (Nano Research, 2019)
Though it is well recognized that the space between graphene cover and the metal substrate can act as a two-dimensional (2D) nanoreactor, several issues are still unresolved, including the role of the metal substrate, the mechanisms ruling water intercalation and the identification of sites at which water is decomposed. Here, we solve these issues by means of density functional theory and high-resolution electron energy loss spectroscopy experiments carried out on graphene grown on (111)-oriented Cu foils. Specifically, we observe decomposition of H2O at room temperature with only H atoms forming bonds with graphene and with buried OH groups underneath the graphene cover. Our theoretical model discloses physicochemical mechanisms ruling the migration and decomposition of water on graphene/Cu. We discover that the edge of graphene can be easily saturated by H through decomposition of H2O, which allows H2O to migrate in the subsurface region from the decoupled edge, where H2O decomposes at room temperature. Hydrogen atoms produced by the decomposition of H2O initially form a chemical bond with graphene for the lower energy barrier compared with other routes. These findings are essential to exploit graphene/Cu interfaces in catalysis and in energy-related applications. [Figure not available: see fulltext.].
Keywords: Decomposition of waters; High resolution electron energy loss spectroscopy; Lower energy barriers; Physico-chemical mechanisms; Theoretical modeling; Two Dimensional (2 D); Water intercalation; Water splitting; graphene/metal interfaces; intercalation; room temperature; water splitting